The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/01.phm.0000091988.20916.ef
|View full text |Cite|
|
Sign up to set email alerts
|

Muscular Atrophy in the Hemiplegic Thigh in Patients After Stroke

Abstract: Muscle volume decreases in the hemiplegic side in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 15 publications
2
50
0
1
Order By: Relevance
“…At 1 month post stroke, no change in lean muscle mass was found in the paretic leg or arm with DEXA imaging, 28 but by 2-4 months a decrease in lean muscle mass was evident in the paretic leg and arm muscles with both DEXA and CT imaging. 28,29,34 In the chronic phase (>6 months after stroke), a decrease in lean muscle mass on the paretic side relative to the non-paretic side was found with both DEXA and CT imaging, 27,31,33,35 meaning that many people with stroke are living with long-term effects of decreased muscle mass in the paretic muscles. A decrease in lean muscle mass with an increase in non-contractile tissue, including fat mass, is common with ageing.…”
Section: Muscle Sizementioning
confidence: 99%
See 2 more Smart Citations
“…At 1 month post stroke, no change in lean muscle mass was found in the paretic leg or arm with DEXA imaging, 28 but by 2-4 months a decrease in lean muscle mass was evident in the paretic leg and arm muscles with both DEXA and CT imaging. 28,29,34 In the chronic phase (>6 months after stroke), a decrease in lean muscle mass on the paretic side relative to the non-paretic side was found with both DEXA and CT imaging, 27,31,33,35 meaning that many people with stroke are living with long-term effects of decreased muscle mass in the paretic muscles. A decrease in lean muscle mass with an increase in non-contractile tissue, including fat mass, is common with ageing.…”
Section: Muscle Sizementioning
confidence: 99%
“…27,29,31,[33][34][35] The studies reviewed found that the change in pennation angle differed for the muscles of the upper and lower extremities, increasing in the former and decreasing in the latter. [39][40][41] Only three studies were identified that examined changes in pennation angle, which makes it difficult to draw conclusions as to whether the differences in pennation angle are related to the function of the muscles (differences in patterns of use between gastrocnemius in the leg and brachialis in the arm) or to their structural composition.…”
Section: Architectural Changes In Muscle After Strokementioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] Musculoskeletal dysfunction is relatively common in patients with chronic conditions such as chronic obstructive pulmonary disease, 37,38 chronic heart failure, 39,40 and stroke. 41,42 This decline in muscle function reduces functional mobility and physical capacity, which, in turn, can result in a limited ability to maintain muscle activity and decreased levels of protein synthesis. [43][44][45][46] However, the exact aetiology of this deterioration is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…The structural properties of chronic stroke patients' skeletal muscles of the paretic side change as a result of a reduction in muscle volume, the shortening of muscle fibers, and a decrease in the activity unit number on the affected side 2,17) . These changes are associated with muscle weakness, spasticity, contracture, and atrophy on the paretic side 3) .…”
Section: Discussionmentioning
confidence: 99%